Awareness of ergonomics for online teaching in school teachers - Baheti, Radhika S.; Ray, Manish M.; Shyam, Ashok; Sancheti, Parag (International Journal Of Community Medicine And Public Health, 2021)
Background: Musculoskeletal disorders (MSDs) have been a well-known health issue in many occupations and its incidence among school teachers is particularly high. The teachers were thrown into a “new normal” of working from home offices because of the COVID-19 pandemic. Online teaching invites its own set of musculoskeletal aches and pains accompanied with eye strain and even hoarseness of voice or discomfort in the throat caused due to speaking for hours at a stretch. Teachers teaching online have to work in a sitting posture for extended periods of time, gaze at the screens of the computer/mobile constantly throughout the task, speak continuously for most hours of their work and make voice modulations for them to be clearly audible over the connection. Hence, this study was conducted to find out the awareness of various ergonomic principles in school teachers conducting online lectures. Methods: The study included 97 participants within the age group of 20-58 years (38.35±10.50) who were sent the Self-made questionnaire via online platform. The questionnaire included several closed ended questions about the ergonomic principles, sitting postures and workstation set ups. The information so obtained was documented and converted into a computer based spread sheet for data analysis. Results: Based on the results obtained, the participants showed reduced levels of ergonomic awareness. Conclusions: The study therefore concluded that the teachers had reduced levels of ergonomic awareness.